The Pattern of and motives for alcohol use among the students at the faculty of Health Care Sciences at the University of Limpopo, Medunsa Campus - Tayob, Sharifa Moosa (University of Limpopo (Medunsa Campus), 2013)
Alcohol use and abuse is highly prevalent among university students and it is a major health concern for universities across the globe. It is important to identify students at risk of, and those who engage in heavy drinking and the reasons thereof so that early identification and referral for intervention can be made before students at risk suffer dire consequences. The aim .of this study was to determine the pattern of alcohol use among the health care science students at the University of Limpopo (Medunsa campus). A quantitative, cross-sectional approach was utilised. Data was gathered by the use of a self administered questionnaire. Stratified and cluster techniques were used to obtain the sample. Descriptive statistics was used to describe data and explore relationships. Relationships between variables of interest were established by using the Spearman's rank correlation coefficient (rho). The prevalence of alcohol use among the participants was relatively low (23%). 15% of respondents were categorized as light drinkers, 3.5% moderate drinkers and 3.5% heavy drinkers. The respondents scored the lowest on the Peer Pressure motive for alcohol use (35.6%) and equal on the Personal Enjoyment and Tension Reduction category, both having mean scores of39% respectively. The Spearman's rho revealed statistically significant relationships among the different types of drinking categories and the following drinking motives: to experience a good time, to feel good, to cheer up and to ease when blamed. This studies finding revealed that the prevalence of alcohol use among health care science students at the University of Limpopo (Medunsa campus) was exceptionally low. The study also brought to light that social motives for drinking was the primary drinking motive and the correlations between the patterns and motives for drinking were only found among four sub categories from the drinkin motives sub-scales.
Thesis (MPH)-- University of Limpopo (Medunsa Campus), 2012.
Keywords: Alcoholism; Alcohol drinking